EXPERIMENTAL STUDY OF NEGATIVE EMOTIONAL STATES IN THE PERIOD OF WAR (Psychology Travelogs, 2023)
To date, there is no such person left in Ukraine who was not affected by the war caused by Russia's aggression. It touches someone directly, someone indirectly, but regardless of how much a person has experienced the course and consequences of the war, this event causes a whole range of negative emotions.The article is devoted to the problem of overcoming negative emotional states during the war. War causes severe stress in a person due to the impact of various extreme events and situations associated with a constant threat to life. In wartime, the amount of stress increases several times, as a person is constantly under the influence of various extreme factors, therefore, we experience negative emotions more often.Such stressors have a negative impact on a person's psyche, disrupting his emotional sphere, causing the development of negative emotional states, in particular, depression and anxiety.War generates a large number of complex and extreme effects on all people - men and women alike. To date, a sufficient number of experimental studies have not yet been conducted, which can be relied upon and give clear statistics of how many percent of people experience one or another negative emotional state or depressive symptoms. However, it is obvious that the trend is moving towards deterioration.Our emotions and feelings directly affect our actions, behavior, activities and, as a result, our lives. Since the negative emotions in the lives of each of us increased significantly during the war, it leaves a certain negative imprint on our lives.The article examines the results of an empirical study of the manifestations of symptoms of the development of depressive states in women during the war. On the basis of the obtained data, the manifestations of depression and anxiety during this period in the subjects were analyzed, which made it possible to conclude about the need for psychological work to overcome the high level of anxiety of women during the war.
Keywords: negative emotions; stress; depression; anxiety; war